PRARANCANGAN PABRIK 2 â ETIL HEKSANOL DARI PROPILEN DAN GAS SINTESIS KAPASITAS 100.000 TON/ TAHUN - , DANU WICAKSONO; , Ir. Supranto, M.Sc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Production of 2 - ethyl hexanol is through three stages of reaction. The first, propylene and synthesis gas is reacted in the oxo reactor with a solution of rhodium catalyst at a pressure of 50 atm and a temperature of 107.5 °C to formnbutanal as the main product, and i-butanal as a byproduct. The second, n-butanal is reacted in the aldol reactor to form 2-ethyl hexenal at a pressure of 3.2 atm and a temperature of 106.16 °C. The next stage is process of hydrogenation of2-ethyl hexenal become 2-ethyl hexanol with Raney Nickel catalyst at a pressure of 25 atm and a temperature of 130 °C. This plant produces 2-ethyl hexanol as much as 100,000 tons / year with a purity of 98%. While the addition of i-butanal 83% and n-butanal 77.4%. The plant needs 9025,839 tonnes/year of propylene, and synthesis gas 6449,2 tonnes/year of raw materials. The utilities needs water at the rate 258318,422 m3/hr, fuel gas at the rate of 2,2653 m3/hr, power 1830,9655 kVA and air for instrumentation and process at the rate of 70,2240 m3/hr. The 2-ethyl hexanol plant will be built in Cilegon, West Java. It needs 140000 m2 area and 427 employees. Based on economic analysis in years 2013, the fixed capital of 2-ethyl hexanol plant is Rp 1.130.631.757.788,19 and US$ 115,370,587.53 and working capital of 2-ethyl hexanol plant is Rp 1.613.500.282.096,38. The manufacturing cost of 2-ethyl hexanol plant is Rp 1.957.419.133.751,83 , and the general expenses of 2-ethyl hexanol plant is Rp 173.621.046.885,47. The result of economic analysis shows that the 2-ethyl hexanol plant produces profit before taxes Rp 574.205.307.822,43 and profit after taxes Rp 287.102.653.911,22. The value of Percent Return of Investment (ROI) before taxes is 50,79 % and after taxes is 25,39 %. The value of Pay Out Time (POT) before taxes is 1,65 years and after taxes is 2,85 years. The value of Break Even Point (BEP) is 43,40 %, Shut Down Point (SDP) is 24,29 %, and Discounted Cash Flow Rate of Return (DCFRR) is 13,7515 %. Based on data above, The 2- ethyl hexanol Plant from propylene and synthesis gas with 100,000 tonnes/year capacity is potential for further evaluation.